2023
DOI: 10.1158/2767-9764.crc-22-0344
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-specific Protease USP36 Associates with the Microprocessor Complex and Regulates miRNA Biogenesis by SUMOylating DGCR8

Abstract: MicroRNA (miRNA) biogenesis is a cellular process that produces mature miRNAs from their primary transcripts, pri-miRNAs, via two RNAse III enzyme complexes: the Drosha-DGCR8 microprocessor complex in the nucleus and the Dicer-TRBP complex in the cytoplasm. Emerging evidence suggests that miRNA biogenesis is tightly regulated by posttranscriptional and posttranslational modifications and aberrant miRNA biogenesis is associated with various human diseases including cancer. DGCR8 has been shown to be modified by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Interestingly, we observed that USP36 strongly binds to pre-rRNA (Chen et al, 2023). The RNA-binding property of USP36 has also been shown by others wherein it binds to long noncoding RNAs (lncRNAs) (Mondal et al, 2018) and microRNAs (Treiber et al, 2017;Li et al, 2023). Indeed, it plays a role in microRNA biogenesis by binding to the microprocessor complex and mediating DGCR8 SUMOylation in the nucleolus (Li et al, 2023).…”
Section: Roles Of Usp36 In Nucleolar Sumoylationsupporting
confidence: 70%
“…Interestingly, we observed that USP36 strongly binds to pre-rRNA (Chen et al, 2023). The RNA-binding property of USP36 has also been shown by others wherein it binds to long noncoding RNAs (lncRNAs) (Mondal et al, 2018) and microRNAs (Treiber et al, 2017;Li et al, 2023). Indeed, it plays a role in microRNA biogenesis by binding to the microprocessor complex and mediating DGCR8 SUMOylation in the nucleolus (Li et al, 2023).…”
Section: Roles Of Usp36 In Nucleolar Sumoylationsupporting
confidence: 70%
“…By using Lipofectamine ® 3000 reagent (Invitrogen, MA, USA), cell transfection was carried out for 48 h as previously reported [ 42 ]. The efficiency of all transfections was examined by detecting both mRNA and protein levels with RT-PCR and western blot, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, it enhances the binding of DGCR8 to pri-miRNAs. Consequently, USP36 controls the processing of pri-miRNA within the nucleolus via the SUMOylation of DGCR8 [22].…”
Section: The Functions Of Usp36 In Nucleolar Protein Sumoylationmentioning
confidence: 99%